Komunitas Burung Berdasarkan Zonasi Ketinggian di Gunung Singgalang, Sumatera Barat - Nova Adri Yanti; Wilson Novarino; Rizaldi Rizaldi (Jurnal Biologi Universitas Andalas, 2015)
Study on bird community based on altitudinal zonation of Singgalang Mountain, West Sumatra was conducted in January 2014. This study aimed to describe community structure the bird from lower to higher elevation of the mountain. This study used point count method along a survey routes from 1300 to 2700 m asl, which is divided into three zones (Zone I: 1300 - 1800 m asl, Zone II: 1800 - 2200 m asl and Zone III: 2200 - 2700 m asl). This study recorded 216 individuals of 38 bird species to 21 families and 9 orders. The highest species diversity and richness was in Zone II. Zone III had low richness and low species diversity but the presence of bird is more evenly distributed. Most of the endemic bird species at Mount Singgalang was found at Zone I (1300 to 2300 m asl). Species richness decreases along increasing the altitudinal zonation of Singgalang Mountain.Key Words : Altitudinal zonation, community, bird, Singgalang Mountain